Penerapan Metode K-Nearest Neighbor pada Sentimen Analisis Pengguna Twitter terhadap KTT G20 di Indonesia - Herda Andriana; Shofa Shofia Hilab; Agustia Hananto (JURIKOM (Jurnal Riset Komputer), 2023)
Indonesia will host the KTT (Konferensi Tingkat Tinggi) G20 summit on the island of Bali on November 15, 2022. The G20 was formed with one goal in mind: to boost the global economy, which had just entered a period of crisis. However, Indonesia's participation as a full member of the Group of Twenty (G20) has sparked controversy among the country's general populace and the population of Indonesia itself, necessitating a thoughtful analysis of the group's motives. Sentiment analysis was gleaned from tweets on KTT G20 posted on the social media platform Twitter. Data scraping yielded a total of 2,500 tweets for inclusion in the collection. Methods for classifying tweets into positive, neutral, and negative groups are required because of the large amount of data that has already been collected. The purpose of this study was to analyze public opinion on Twitter during the KTT G20. The data was processed using the Orange neural network using a number of tools and the K-Nearest Neighbor method, yielding a total of 1,107 tweets that were successfully added to the original set, with an average recall and precision of 99%. According to the analysis of sentiment, there were 89 negative tweets, 614 neutral tweets, and 404 positive tweets, with the most common emotions being happiness, surprise, and fear